Juridical Review of The Cancellation of Electronic Land Title Certificates Based on The Regulation of The Minister of Agrarian Affairs and Spatial Planning/Head of The National Land Agency of The Republic of Indonesia Number 21 of 2020 - Pingkan Dewi Kaunang (International Journal of Law and Society, 2025)
A certificate serves as strong evidence of land ownership rights. In line with technological advancements, the government, through the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency, has introduced a legal product in the form of an Electronic Certificate. This Electronic Certificate, also known as e-Certificate, is issued as a result of an electronic land registration process. As a legal product of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency, the Electronic Certificate constitutes valid and strong evidence of land ownership rights. However, in the process of land registration leading to the issuance of the Electronic Certificate, as well as in other related aspects, errors may occur, resulting in administrative and/or juridical defects. Moreover, the Electronic Certificate may also become an object of a court decision. Consequently, the Electronic Certificate can be subject to cancellation, which may be processed based on the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 21 of 2020 on the Handling and Resolution of Land Cases. This study employs a normative juridical research method, utilizing a statute approach as its legal analysis framework.